2021
DOI: 10.3390/polym13101623
|View full text |Cite
|
Sign up to set email alerts
|

Gr/3D–ZnO Nanocomposites as Humidity Sensors with Enhanced Sensing Response

Abstract: This work introduces a novel humidity sensor based on a nanocomposite material comprising graphene decorated with three-dimensional flower-like structures of zinc oxide (Gr/3D–ZnO) fabricated via a hydrothermal method with various weight percentages of graphene. The surface structure and morphology of the Gr/3D–ZnO nanocomposite were analyzed using XRD, EDS, SEM, TEM, and Raman spectroscopy. The influence of humidity on the electrical properties of the nanocomposite was also investigated. Experiment results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…As a representative type, the Janus structure of a bilayer film can more effectively and intuitively express the mechanical work generated by external stimulation in different material layers. Recently, graphene and its derivative graphene oxide (GO) have been introduced to design moisture actuators due to their large surface area, mechanical flexibility, and good chemical and physical stability properties. Our comprehensive analysis found that the design principle of graphene moisture drives of common Janus structures can be roughly summarized into two categories: the first class is based on the composite structures of different materials, which uses the hydrophilic differences between different materials to achieve energy conversion and deformation. This type of moisture drive has a clear driving mechanism and a controlled deformation direction, but large-angle deformation or motion still needs to be improved. The other is that the same material utilizes structural differences to achieve a moisture-driven response. , Consequently, it is expected that moisture actuators with higher comprehensive performance can be prepared through reasonable material selection and scientific structural design.…”
Section: Introductionmentioning
confidence: 99%
“…As a representative type, the Janus structure of a bilayer film can more effectively and intuitively express the mechanical work generated by external stimulation in different material layers. Recently, graphene and its derivative graphene oxide (GO) have been introduced to design moisture actuators due to their large surface area, mechanical flexibility, and good chemical and physical stability properties. Our comprehensive analysis found that the design principle of graphene moisture drives of common Janus structures can be roughly summarized into two categories: the first class is based on the composite structures of different materials, which uses the hydrophilic differences between different materials to achieve energy conversion and deformation. This type of moisture drive has a clear driving mechanism and a controlled deformation direction, but large-angle deformation or motion still needs to be improved. The other is that the same material utilizes structural differences to achieve a moisture-driven response. , Consequently, it is expected that moisture actuators with higher comprehensive performance can be prepared through reasonable material selection and scientific structural design.…”
Section: Introductionmentioning
confidence: 99%